Pattern control via diffusion interaction - Ruiz-Balet, Domènec; Zuazua Iriondo, Enrique (2024)
We analyse a dynamic control problem for scalar reaction-diffusion equations, focusing on the emulation of pattern formation through the selection of appropriate active controls. While boundary controls alone prove inadequate for replicating the complex patterns seen in biological systems, particu- larly under natural point-wise constraints of the system state, their combination with the regulation of the diffusion coefficient enables the successful generation of such patterns. Our study demonstrates that the set of steady-states is path-connected, facilitating the use of the staircase method. This approach allows any admissible initial configuration to evolve into any stationary pattern over a sufficiently long time while maintaining the system’s natural bilateral constraints. We provide also examples of complex patterns that steady-state configurations can adopt.
https://cris.fau.de/converis/publicweb/Publication/325045502